Patient Perspectives on Detox: Practical and Personal Considerations through a Lens of Patient-Centered Care. (19th September 2021) - Sharp, Amanda; Armstrong, Amanda; Moore, Kathleen; Carlson, Melissa; Braughton, David
Abstract: Inpatient detoxification is often required before a client can move on to additional substance abuse treatment services. Although often short-term, time spent in inpatient detoxification tends to have long-lasting effects on the recovery process. This qualitative study focuses on one treatment facility in Tampa, Florida that offers a range of recovery services, including inpatient detox and outpatient treatment. Focus groups ( N   =  70 participants) captured client perceptions of direct clinical care operations, access to resources, and relationships with direct care staff within the inpatient detox program. Perceptions were then assessed using a thematic analysis approach with attention to the literature on person-centered care best practices, behavior change, and patient engagement theories to better understand how facility practices affect treatment engagement and retention. Findings elucidated several practical facilitators and barriers to recovery such as facility resources, services offered, transition to aftercare, and sustainability of treatment. Findings also illuminated several personal facilitators and barriers including patient-staff interactions, personal motivation, and family and community support. The resulting recommendations for practice and research are discussed.